Thermodynamic Analysis for Buoyancy-Induced Couple Stress Nanofluid Flow with Constant Heat Flux - Samuel O. Adesanya; Hammed A. Ogunseye; J. A. Falade; R.S. Lebelo (Entropy, 2017)
This paper addresses entropy generation in the flow of an electrically-conducting couple stress nanofluid through a vertical porous channel subjected to constant heat flux. By using the Buongiorno model, equations for momentum, energy, and nanofluid concentration are modelled, solved using homotopy analysis and furthermore, solved numerically. The variations of significant fluid parameters with respect to fluid velocity, temperature, nanofluid concentration, entropy generation, and irreversibility ratio are investigated, presented graphically, and discussed based on physical laws.